NEW PUBLIC DIPLOMACY IN THE NEW MILLENNIUM - Yenigun, Cuneyt; Yari, Houchang Hassan; Maani, AbdullahAl (The journal of contemporary issues in business and government, 2021)
The new instruments of public diplomacy are deepening and diversifying in the contemporary world. Today, the range of phenomena that could be used as new tools of public diplomacy has grown. Some of the new instruments in the new millennium could be highlighted as diaspora, international conferences, scholarships, journals, advertorials, towering personalities, sport, dominant culture, relations with Intergovernmental institutions, focus on international civil society groups, news agencies, social media tools, cultural centers, universal kitchen, music and exchange programs, in addition to the older ones.The number of these public diplomacy tools that is updatedin this research is 37 as seen in the figure. Old public diplomacy tools are not easy to reshape or create such as organizing diaspora, flouring your language, kitchen or culture. But majority of the new public diplomacy tools could be created in a mid or short term such as establishing university chairs, television channels, communicating social media groups, organizing frequent international conferences, publishing journals, initiating quality movies and serials and establishing good relations with the international NGOs, CSGs and think-tanks. All of those instruments need money, but this should be perceived as soft power investment.